Regulation of Src family kinases by muscarinic acetylcholine receptors in heterologous cells and neurons - Mao, Li-Min; Young, Lexi; Chu, Xiang-Ping; Wang, John Q. (Frontiers in Molecular Neuroscience, 2024)
Five muscarinic acetylcholine (mACh) receptor subtypes are divided into two classes: the M1 class (M1, M3, and M5) and the M2 class (M2 and M4). The former is coupled to Gq proteins, while the latter is coupled to Gi/o proteins. Accumulating evidence indicates that mACh receptors play a significant role in the regulation of the Src family kinase (SFK), a subfamily of non-receptor tyrosine kinases. mACh receptors exert their roles in a subtype-dependent fashion and preferentially target Src and Fyn, two members of SFKs that are expressed in the brain and enriched at synaptic sites. While the M1 receptor positively modulates SFK activity, the M4 receptor inhibits it. By modulating SFKs, mACh receptors are actively involved in the regulation of expression and function of a variety of receptors, structural proteins, and signaling molecules. In particular, the M4 receptor and the dopamine D1 receptor are coexpressed in striatonigral projection neurons of the striatum. Gi/o-coupled M4 and Gq-coupled D1 receptors antagonistically regulate SFK activity, thereby forming a dynamic balance controlling glutamate receptor activity, excitability of neurons, and synaptic plasticity. In summary, mACh receptors play a crucial role in regulating SFK activity in heterologous cells and neurons.